ANALISIS RESIKO PRODUKSI DAN PENDAPATAN BUDIDAYA TAMBAK UDANG RAKYAT DI KELURAHAN LABUHAN DELI, KECAMATAN MEDAN MARELAN, KOTA MEDAN - Saragih, Nani Sura; Sukiyono, Ketut; Cahyadinata, Indra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
The aim of the research was (1) to analyze the risk of production (2) to analyze farmer’s income, and (3) to analyze the risk of income. The research was conducted from June to July in 2014. Research area was chosen purposively in Urban Village Labuhan Deli , Sub District Medan Marelan, Medan City. The number of samples were 57 samples drawn by a simple random sampling. Data was analyzed using analisys of income and analisys of risk. The research result showed that shrimp cultivation earned Rp 19.571.547/Ha/Year. Meanwhile, based on the value of the coefficient variation’s production that was 0.04 and the lower earnings was 142,60 Kg, it show that there was a little of risk faced by farmers. Then, based on the value of the coefficient variation’s income that was 0.017, it showed that there was a little of risk faced by farmers and the lower earnings limit of shrimp cultuvation was Rp 6.304.872,84/Ha/Year. This showed the lowest income that may be accepted by the farmers.